Bioremediation of Direct Blue 14 and Extracellular Ligninolytic Enzyme Production by White Rot Fungi: Pleurotus Spp. (11th June 2013) - Singh, M. P.; Vishwakarma, S. K.; Srivastava, A. K.
Abstract : In the present investigation, four species of white rot fungi ( Pleurotus ), that is, P. flabellatus, P. florida, P. ostreatus and P. sajor-caju were used for decolorization of direct blue 14 (DB14). Among all four species of Pleurotus, P. flabellatus showed the fastest decolorization in petri plates on different concentration, that is, 200 mg/L, 400 mg/L, and 600 mg/L. All these four species were also evaluated for extracellular ligninolytic enzymes (laccase and manganese peroxidase) production and it was observed that the twelve days old culture of P. flabellatus showed the maximum enzymatic activity, that is, 915.7 U/mL and 769.2 U/mL of laccase and manganese peroxidase, respectively. Other three Pleurotus species took more time for dye decolorization and exhibited less enzymatic activities. The rate of decolorization of DB14 dye solution (20 mg/L) by crude enzymes isolated from P. flabellatus was very fast, and it was observed that up to 90.39% dye solution was decolorized in 6 hrs of incubation.